2017
DOI: 10.1002/jcb.26490
|View full text |Cite
|
Sign up to set email alerts
|

MiR 376c inhibits osteoblastogenesis by targeting Wnt3 and ARF‐GEF‐1 ‐facilitated augmentation of beta‐catenin transactivation

Abstract: Wnt signaling pathway plays important role in all aspects of skeletal development which include chondrogenesis, osteoblastogenesis, and osteoclastogenesis. Induction of the Wnt-3 signaling pathway promotes bone formation while inactivation of the pathway leads to bone related disorders like osteoporosis. Wnt signaling thus has become a desired target to treat osteogenic disorders. MicroRNAs (miRNAs) represent an important category of elements that interact with Wnt signaling molecules to regulate osteogenesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…WNT3A expression was variable between cell populations and passages, although WNT3A was expressed significantly more in young female 1 hMDSCs compared to young male 1 hMDSCS . Our in vitro histology, however, demonstrated that young male 1 hMDSCs were more osteogenic than young female 1 hMDSCs.…”
Section: Discussionmentioning
confidence: 54%
“…WNT3A expression was variable between cell populations and passages, although WNT3A was expressed significantly more in young female 1 hMDSCs compared to young male 1 hMDSCS . Our in vitro histology, however, demonstrated that young male 1 hMDSCs were more osteogenic than young female 1 hMDSCs.…”
Section: Discussionmentioning
confidence: 54%
“…In the predicted ceRNA networks, one combination of circ-GNB5, circ-HERC1, circ-KMT2A, circ-LTBP2, hsa-miR-24-3p and the Wnt3 gene, another comprised of circ-LTBP2, circ-MCF2L2, circ-MDN1, circ-MYH9, circ-PLPPR4, circ-RAB31, circ-SMARCH2, circ-SPEG, circ-SYNM, circ-TANGO6, hsa-miR-5195-3p and the Wnt4, IGF1 genes, the third consists of circ-ADAMTS13, circ-ARHGAP32, circ-BRPF3, circ-CARD8, circ-CCDC88C, circ-COL4A2, circ-DGKD, circ-DIP2C, circ-DYNC1H1, circ-FAT3, circ-LTBP2, hsa-let-7b-5p and CHRD, three networks communicated with each other through the core hub circ-LTBP2. Based on the previous prediction, it's target mRNAs including wnt3, wnt4, CBFB, IGF1 and CHRD are recognized osteogenic marker genes (Kureel et al, 2017;Qin et al, 2015;Lindsey, Rundle & Mohan, 2018). What's more, circ-LTBP2 has not been reported yet.…”
Section: Discussionmentioning
confidence: 97%
“…Increasing evidence shows that Wnt/β-catenin axis was regulated, for example, by miR-25, -376c, -21, -34a miRNAs in OS progression (43)(44)(45). Wnt/β-catenin signaling pathway modulates various genes that in turn regulate a diversity of cell functions such as proliferation, differentiation and morphogenesis, and β-catenin was proved to enhance progression, invasion and tumorigenesis in cancers (46).…”
Section: Discussionmentioning
confidence: 99%